2014
DOI: 10.1038/leu.2014.44
|View full text |Cite
|
Sign up to set email alerts
|

BCL-2 family proteins as 5-Azacytidine-sensitizing targets and determinants of response in myeloid malignancies

Abstract: Synergistic molecular vulnerabilities enhancing hypomethylating agents in myeloid malignancies have remained elusive. RNA-interference drug modifier screens identified antiapoptotic BCL-2 family members as potent 5-Azacytidine-sensitizing targets. In further dissecting BCL-XL, BCL-2 and MCL-1 contribution to 5-Azacytidine activity, siRNA silencing of BCL-XL and MCL-1, but not BCL-2, exhibited variable synergy with 5-Azacytidine in vitro. The BCL-XL, BCL-2 and BCL-w inhibitor ABT-737 sensitized most cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(170 citation statements)
references
References 47 publications
6
160
1
3
Order By: Relevance
“…Owing to the high level of heterogeneity of human MDS and in accordance with previous publications on myeloid malignancies, 40 we found inter-individual differences in drug sensitivity. 27 Sample two and three proved to be highly sensitive to ABT-737, with~50% of cells undergoing cell death at doses as low as 10 nM. Sample one was more resistant showing a drop in viability at higher doses (Supplementary Figure 2A).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Owing to the high level of heterogeneity of human MDS and in accordance with previous publications on myeloid malignancies, 40 we found inter-individual differences in drug sensitivity. 27 Sample two and three proved to be highly sensitive to ABT-737, with~50% of cells undergoing cell death at doses as low as 10 nM. Sample one was more resistant showing a drop in viability at higher doses (Supplementary Figure 2A).…”
Section: Resultsmentioning
confidence: 97%
“…These inter-individual differences in BCL-2 protein expression were also found in AML, where BCL-2 expression varied substantially between samples from a given French-AmericanBritish subgroup. 27 Given the critical role of MCL-1 as a resistance biomarker, the detection of protein expression by intracellular flow cytometry might serve as a reasonable way of screening patients before BH3-mimetic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Because the functional redundancy of Bcl-2 antiapoptotic proteins is the major cause of resistance to selective Bcl-2 antagonists (eg, ABT-199), concomitant inhibition of multiple Bcl-2 proteins can presumably overcome this resistance. This notion is supported by our finding that AML cells with high Mcl-1 expression were highly resistant to Bcl-2/Bcl-xL inhibitor ABT-737, whereas all AML cell lines tested showed similar sensitivity to the pan-Bcl-2 inhibitor (-)BI97D6.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observation that these LSCs, especially those harboring a IDH1/2 mutation [111], are characterized by an aberrant overexpression of BCL-2 which mediates mitochondrial respiration (the only source of their low energy requirement) makes them suitable targets for BCL-2 inhibitors [83]. Various studies have demonstrated that these inhibitors have modest activity when employed as single agents, but are much more effective when combined with daunorubicin, PI3K inhibitors [112], 5-Azacytidine [113] and mTOR inhibitors [114]. In addition, BCL-2 proteins might be more effectively inhibited by pan-Bcl-2 inhibitors that in contrast to ABT compounds block the expression of Mcl-1, an anti-apoptotic protein with a critical role in leukemic cell survival and drug resistance [115,116].…”
Section: Potential Targetsmentioning
confidence: 99%